2018
DOI: 10.1108/ijlss-07-2017-0076
|View full text |Cite
|
Sign up to set email alerts
|

Identify critical success factors to implement integrated green and Lean Six Sigma

Abstract: Purpose The purpose of this paper is analysis of Green and Lean Six Sigma, based on the success factors in its use through a well thought-out literature review, is being planned; a framework has been integrated in a productive manner with the Green and Lean and Six Sigma methods so as to incorporate and actualize the execution. Design/methodology/approach The methodology consists of comparative investigation of Green, Lean management and Six Sigma using open written work, essential analysis at data and maste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 40 publications
3
42
0
1
Order By: Relevance
“…As part of the Six Sigma approach, a clear statement of the problem was drafted at the start of the project. Consistent with evidence of previous research (Mishra, 2018;Pyzdek, 2003), the scoping exercise largely consisted of ensuring that team members understand the nature of the problem and what is expected of them. A clear and shared understanding of the problem and the process at the early stages enabled working towards a common goal and channelling of team members' efforts in the right direction, avoiding any ambiguity or confusion.…”
Section: Discussion Of the Resultsmentioning
confidence: 77%
“…As part of the Six Sigma approach, a clear statement of the problem was drafted at the start of the project. Consistent with evidence of previous research (Mishra, 2018;Pyzdek, 2003), the scoping exercise largely consisted of ensuring that team members understand the nature of the problem and what is expected of them. A clear and shared understanding of the problem and the process at the early stages enabled working towards a common goal and channelling of team members' efforts in the right direction, avoiding any ambiguity or confusion.…”
Section: Discussion Of the Resultsmentioning
confidence: 77%
“…There exist few research studies that have identified the success factors of GLSS and investigated the interrelationship between the individual approaches. For example, Mishra [25] has identified five critical success factors of GLSS which are: (1) management and employee commitment, (2) organization's readiness to execute GLSS strategy, (3) selection and prioritization of GLSS projects, (4) provision of resources and training for GLSS implementation, and (5) focus on evaluation and results of GLSS program. Kaswan and Rathi [56] have determined 12 critical success factors and prioritize seven of these (based on experts' opinions) [90] by utilizing the best worst method (BWM), which can facilitate organizations in ranking these factors at the preliminary stage of GLSS program.…”
Section: Critical Success Factors Of Glss Approachmentioning
confidence: 99%
“…Few studies have identified the theoretical constructs of a GLSS approach such as drivers, critical success factors (CSFs), tools and techniques, barriers, and outcomes individually [2,22,24,25]. However, there is little research that addresses the above GLSS constructs as a consolidated approach in reducing environmental impacts of organizations [10,19].…”
Section: Introductionmentioning
confidence: 99%
“…The use of Six Sigma comes with a clear focus on achieving quantifiable and measurable financial returns to an organization"s bottom line. In examining the present state of Six Sigma approach in service based industries, [5] prescribe ways in which organizations can actively implement the approach for positive results. Studies by [17]- [20] investigate the success factors organizations should check for while implementing Six Sigma.…”
Section: Application Of Six Sigmamentioning
confidence: 99%
“…One definition of quality in education by the authors [1]- [3] stated that the quality in education "focusing on meeting a pre-defined set of standards, specifications, and requirements, or focusing on exceeding the highest standards in pursuit of excellence and exclusivity". Other definition by the authors [4], [5] stated the quality in education can be defined as "focusing on accountability to the public or providing a transformative learning experience to benefit students and employers".…”
Section: Introductionmentioning
confidence: 99%